Silly Tilly's Thanksgiving dinner - Hoban, Lillian (New York : Scholastic, 1990)
Forgetful Silly Tilly Mole nearly succeeds in ruining her Thanksgiving dinner, but her animal friends come to the rescue with tasty treats.
"Ages 4-8"--jkt.
350
Keywords: Thanksgiving Day -- Fiction; Moles (Animals) -- Fiction; Animals -- Fiction